2002
DOI: 10.2174/1381612023393198
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based Design of Mimetics for Granulocyte-macrophage Colony Stimulating Factor (GM-CSF)

Abstract: Granulocyte-macrophage colony stimulating factor (GM-CSF) activity has been linked to pro-inflammatory effects in autoimmune syndromes, such as rheumatoid arthritis. Thus GM-CSF mimetics with antagonist activity might play a therapeutic role in these diseases. The human GM-CSF core structure consists of a four alpha-helix bundle, and GM-CSF activity is controlled by its binding to a two-subunit receptor. A number of residues located on the B and C helices of GM-CSF are postulated to interact with the alpha cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…IL-17 shows properties similar to those of IL-1β and TNF-α. They induce in vitro the synthesis of nitric oxide and metalloproteases by chondrocytes and the production of IL-6 and IL-8 by fibroblasts [16]. Eotaxin-1 plays an important role in cartilage degradation in OA [17].…”
Section: Resultsmentioning
confidence: 99%
“…IL-17 shows properties similar to those of IL-1β and TNF-α. They induce in vitro the synthesis of nitric oxide and metalloproteases by chondrocytes and the production of IL-6 and IL-8 by fibroblasts [16]. Eotaxin-1 plays an important role in cartilage degradation in OA [17].…”
Section: Resultsmentioning
confidence: 99%
“…The grafting of a binding epitope on a folded, stable protein is a well-established approach to the design of biologically active miniature protein. [5][6][7][8][9][10] In this paper, we are applying this approach to the display of post-translationally modified epitopes. Ideally, a scaffold should be stable and monomeric at physiological conditions, soluble, and structurally characterized.…”
mentioning
confidence: 99%
“…One possible approach to facilitate the use of Gc-MAF consists of the design of a miniaturized protein analogue on which the active site of Gc-MAF could be displayed. The grafting of a binding epitope on a folded, stable protein is a well-established approach to the design of biologically active miniature protein. In this paper, we are applying this approach to the display of post-translationally modified epitopes. Ideally, a scaffold should be stable and monomeric at physiological conditions, soluble, and structurally characterized.…”
mentioning
confidence: 99%
“…This may be partly related to uncertainties in the determination of the domains of GM-CSF involved in binding to its protein receptor (14). Moreover, despite the fact that conserved amino acid sequences corresponding to heparin-binding motifs have been identified (namely the XBBXBX and XBBBXXBX motifs, where B corresponds to a basic residue) (15), a large number of reports have also shown that heparin/heparan sulfate-binding sites in proteins are not always or necessarily defined by a unique sequence or structural motif (16).…”
mentioning
confidence: 99%